Optimization of drying temperature and time in gesho “Rhamuns Prinoide” leaf powder processing as hop substitute in commercial beer brewing industries - Ayalew Demissew; Mehiret Mulugeta (Journal of Food Science and Hygiene, 2017)
Beer is typically brewed from four basic ingredients (water, a starch source, brewer’s yeast and flavoring agent such as hops). In Ethiopian case hops are coasty ingredient of beer which is imported with hard currency of the country. But this flavoring agent (hops) in beer production can also be substituted by locally available flavouring agent called gesho “Rhamuns Prinoide” leaf. In this study the effect of drying temperature and time on brewing components of gesho “Rhamuns Prinoide” leaf was examined using oven dryer. Brewing components of gesho “Rhamuns Prinoide” leaf were compared by taking the commercial hop brewing component as a standard. Drying temperature and time have a significant effect (P< 0.05) on major beer brewing components (Resin, Hop oil, Polyphenol, Mineral and Protein) of gesho leaf. Not only drying temperature and time but also the interaction effect has significant effect on these major brewing components of the leaf. The optimal drying temperature and time of gesho leaf was also determined to commercialize the gesho leaf powder or pellet as hop substitute in commercial beer brewers as flavouring
Keywords: Gesho